Assessing The Role Of Hospital Ownership On Total Factor Productivity Changes In Qazvin Hospitals Using Malemquistٰs Index And DEA - Nima Rahmani; Abdollah Keshavarz; Seyed Saeed Tabatabaei; Rohollah Kalhor (Tehran University of Medical Sciences, 2012)
Background and Aim: In many countries, hospitals have triple ownership (governmental or public, for-profit, and not-for-profit). Numerous studies have been performed in order to investigate the differences among these hospitals in accordance to expenditures, presentation of uncompensated therapeutic services, number of outgoing patients and other measurement devices of hospital performance. The aim of this research was to investigate the role of ownership on total Factors Productivity changes in Qazvin`s selected hospitals. Materials and Methods: Descriptive-analytic study was conducted in three periods of time from 2005 to 2007 in 8 selected hospitals of Qazvin. Inclusion criteria included the active beds and the value of intermediate consumptions in hospitals.The exclusion criteria included the total number of inpatient and surgical operations. Data collection tool, was researcher-designed checklist. Data were analyzed using DEAP 2/1 software and ANOVA, HSD and TUKEY tests. Results: There was a significant difference between the mean productivity of three hospital groups due to the existence of various ownership(p=%012), Also a significant difference was observed between the mean of technological efficiency of the three groups of hospitals(p=%006), No significant differences was found between the mean of technical efficiency of the three groups of hospitals(p=%23). Conclusion: Cause of the variation in total factor productivity in private hospitals, is due to their suitable production technology which is always improved. But in respect to their efficiency promotion and optimization of production and products, there was no distinguishing difference with other hospitals.